Impact of Annealing on CuInSe2 Thin Films and Its Schottky Interface - U. Parihar; J.R. Ray; N. Kumar; R. Sachdeva; N. Padha; C.J. Panchal (Журнал нано- та електронної фізики)
The room temperature current–voltage (I-V) characteristics of the Al/p-CuInSe2 Schottky Diodes fabricated on thermally evaporated CIS thin films, before and after annealing, were studied. Prior to their diode formation, the undertaken CIS thin films were compared on the basis of structural, morphological and electrical investigations. Wherein, annealed films showed an increase in the grain size and carrier concentration values while decrease in resistivity. I-V analysis of the Schottky diodes depicted decrease in the barrier heights and increase in ideality factors of those formed on annealed films. The diodes, thus, indicated the existence of barrier inhomogenity at the M-S interface. The annealed Schottky diodes also demonstrated better ideality factor values with increased thickness of CIS layer.